Pengembangan Ehon Sebagai Media Pembelajaran Bahasa Jepang Untuk Menuntun Kemampuan Berpikir Kritis Siswa Jurusan Pariwisata Pada SMK di Singaraja - Rahman , Zaifur; Sadyana, I Wayan; Mardani, Desak Made Sri (STKIP AGAMA HINDU SINGARAJA, 2024)
This study aims to develop learning media in the form of Ehon for Japanese language learning at Singaraja Vocational School majoring in tourism and to determine the feasibility of the media being developed. The type of this research is research and development (Research and Development). The research model used in this study is an adaptation of the Borg and Gall (1983) model in Puslitjaknov (2008: 11) which consists of four stages of development including preliminary studies, planning and product development, expert validation and limited trials. The product produced is Ehon media which consists of 8 material chapters, in each chapter consisting of stories, questions and conversations to guide students' critical thinking skills. Data collection was carried out using interviews and questionnaires in the form of expert test questionnaires (matter expert tests, media expert tests) and product trials in order to produce good products. Based on the results of the questionnaire, the score obtained from material experts was 75 (appropriate), from media experts namely 100 (very appropriate). The score obtained from the results of the limited trial questionnaire with the teacher was 100 (very appropriate) and the results of the limited trial with students were 97% (very feasible). Thus, the developed Ehon media can be used as a learning support medium and guides students' critical thinking skills in learning Japanese in accordance with the tourism major.